The Pragmatics of Politeness in Post Office Service in Ibadan Metropolis, Nigeria (2011)
Although politeness has been well researched in political, medical, media and commercial transactions, it has not been well considered in the area of service delivery in the post offices in Nigeria where it is perceived that the staff exhibit unfriendly attitude to customers. This study, therefore, explores politeness in service encounters in the post offices in Ibadan metropolis with the view to establishing the existence of politeness in the transactions in the establishment, identifying politeness strategies used and highlighting the contributions of job satisfaction, domestic problem, gender, educational status of staff, appearance of customers to the exhibition of politeness during transactions. The study was carried out within a combined theoretical framework of genre classification propounded by Eija Ventola, Suzzane Eggins and Diana Slade, which focuses on the optional and obligatory stages during transaction, Lim's and Bowers' facework theory that locates nuance polite expression orientations and Spencer-Oatey’s rapport managements which categorises rapport strategies. Five post offices from the five local government areas within Ibadan metropolis were randomly selected. Forty seven willing clients and 35 counter attendants were orally interviewed while questionnaires were administered to 35 willing clients and 35 counter attendants respectively. Post office service questionnaire, interviews and participant observation were used for data collection. Transactions in Yoruba were translated into English. Data were analysed using content analysis T-test, ANOVA and Pearson r correlation. Contrary to the belief among many Nigerians that post office staff were generally impolite, a high degree of politeness was established in the staff’s interactions with customers. Although some impoliteness existed, the degree did not affect the transactions. Both the staff and the customers made use of ‘solidarity’, ‘approbation’ and ‘tact’ politeness strategies. The staff frequently used covert ‘solidarity’ expressed by silent acceptance and readiness to offer service. ‘Tact’ came in the form of ‘advice’ and ‘order’ in answer to requests. ‘Approbation’ took the form of ‘suggestion’. Both tact and approbation strategies are power implicated. Customers on the other hand, engaged overt solidarity strategies such as ‘agreement’, ‘cooperation’ and ‘greeting’. ‘Thanking’ was the main approbation strategy; and ‘please’ and implied ‘need’ were used as ‘tact’ strategies when making requests and clarifications. There were relationship between appearance and politeness (r=0.39), job satisfaction and politeness (r=0.29). However, domestic problem, educational status and sex of did not influence the expression of politeness There was a considerable degree of politeness in Ibadan post office service encounters, which facilitated interactions between the staff and the customers.